Comprehensive analysis of the effect of electron irradiation on oligo(ethylene glycol) terminated self-assembled monolayers applicable for specific and nonspecific patterning of proteins - Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
Controlled modification of protein-repelling self-assembled monolayers (SAMs) of oligo(ethylene glycol) (OEG) terminated alkanethiols (AT) by electron irradiation was investigated, and the usability of these templates for the fabrication of proteins patterns by electron beam lithography was explored. The attachment of proteins was performed either directly after irradiation, based on nonspecific interaction with the modified SAM constituents, or after the successive exchange reaction with molecular substituents bearing special receptor group for protein adsorption, based on the respective specific interaction. Characteristic dose ranges for the above approaches, viz. direct writing (DW) and irradiation-promoted exchange reaction (IPER), were defined. On the basis of these findings, patterns of both specifically and nonspecifically bound proteins of various shapes and on different length scales were fabricated in the OEG-AT templates. In addition, a simple, one-step irradiation process was suggested to prepare multiprotein patterns. As an example, side-by-side patterning of bovine serum albumin and avidin is described.